Computer‐Driven Development of Ylide Functionalized Phosphines for Palladium‐Catalyzed Hiyama Couplings. Issue 9 (24th January 2023) - Goebel, Jonas F.; Löffler, Julian; Zeng, Zhongyi; Handelmann, Jens; Hermann, Albert; Rodstein, Ilja; Gensch, Tobias; Gessner, Viktoria H.; Gooßen, Lukas J.
Abstract: Palladium‐catalyzed couplings of silicon enolates with aryl electrophiles are of great synthetic utility, but often limited to expensive bromide substrates. A comparative experimental study confirmed that none of the established ligand systems allows to couple inexpensive aryl chlorides with α‐trimethylsilyl alkylnitriles. In contrast, ylide functionalized phosphines (YPhos) led to encouraging results. A statistical model was developed that correlates the reaction yields with ligand features. It was employed to predict catalyst structures with superior performance. With this cheminformatics approach, YPhos ligands were tailored specifically to the demands of Hiyama couplings. The newly synthesized ligands displayed record‐setting activities, enabling the elusive coupling of aryl chlorides with α‐trimethylsilyl alkyl nitriles. The preparative utility of the catalyst system was demonstrated by the synthesis of pharmaceutically meaningful α‐aryl alkylnitriles, α‐arylcarbonyls and biaryls. Abstract : Ylide functionalized phosphines were tailored supported by computational inverse catalyst design to fit the requirements of mild Hiyama couplings of aryl chlorides. YPhos/Pd catalyst is highly efficient for the coupling with aryl chlorides in general, and the reaction shows excellent functional group compatibility.